Breast feeding practice in a selected peri urban area of Bangladesh (Bangladesh Journal of Medicine, 2022)
Background: Exclusive breastfeeding (EBF) offers optimum growth and development up to first six month of life. In Bangladesh, 55% of children less than 6 months of age are exclusively breastfed according to BDHS 2014.the aim of the study is to assess the exclusive breast feeding practice and associated factors among children in peri- urban area of Bangladesh.Methods: This is a cross sectional observational study conducted at Jhalkuri under Narayanganj districts during the period of July to December 2014. Total 109 mothers having infants aged 6-12 months interviewed and included in this study.Results: It was found that only 26(24%) mother went for regular antenatal checkup and remaining 83 (76%) had irregular antenatal check up. But none of them got breastfeeding advice during antenatal visit. Knowledge about breast milk as first food in 44(40%) mother. Mother informed to breast feeding exclusively upto six months only 53 (48%).Breastfeeding was initiated with in 1 hour of birth in 42(39%) cases and 67 (61%) cases after 1hour of birth. Exclusive breastfeeding (EBF) was found in 43 (40%) children. Among them 34 (79%) were children of housewife mothers. Mixed feeding (breast milk plus formula/ cow’s milk) was given to 52 children among them 25 (49%) were the children of housewife mothers. Only formula milk was given to 14 children of them 5(35%) were the children of housewife mothers. Exclusive breast milk was not given by 26(39%) mothers due to job or other occupation whereas 40(61%) mother did not give EBF due to insufficient breast milk.Conclusion: In the study rate of exclusive breast feeding was 40%. This is lower compare to national level. This study also showed that frequency of exclusive breast feeding practice was lower in working mothers than housewife mothers. This study also showed that the speculation of not getting sufficient milk was one of the main reasons for not giving exclusive breastfeeding.Bangladesh J Medicine 2022; 33: 274-279